Plants Diversity for Ethnic Food and the Potentiality of Ethno-culinary Tourism Development in Kemiren Village, Banyuwangi, Indonesia - Wahyu Kusumayanti Putri; Luchman Hakim; Serafinah Indriyani (Program Pascasarjana, 2017)
Recent rapid grow of culinary tourism has significant potential contribution to enhancing biodiversity conservation especially biodiversity of local plant species for local food and food preparation tradition in local community. Ethnic food has been explored as one of the indigenous resources for community-based tourism, in which it is important in community development and biodiversity conservation. The aim of the study was to describe the involvement of plant in local cuisine and the concept of ethno-culinary tourism products development. The research was based on ethno-botanical study through observation and interviews with local community and tourism stakeholder in Kemiren Village, Banyuwangi. This study found that there was 108 ethnic food menu in Kemiren Village. There are 67 species of 35 plant family were used in local cuisine. Kemiren Village has been identified rich in term of traditional culinary which are able to be developed as attractive cuisine in culinary tourism.Keywords: culinary tourism,Â ethnicfood, Kemiren Village.Â